Consumer Trust as a Mediator: The Influence of Price Perception and Brand Image on School Choice Decision (Case Study at Ar-Rahman Excellence Junior High School) - Desy Lestari; Hari Muharam; Agus Setyo Pranowo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research aims to determine the influence of price perception, brand image, and consumer trust on the decision to choose Ar-Rahman Excellent Junior High School, which is expected to provide input for the institution to increase the number of new student admissions each year. The sample in this study consists of parents of students who enrolled in the 2022/2023 academic year up to 2024/2025. Sampling was conducted using probability sampling with the simple random sampling method. Data analysis using Structural Equation Modeling (SEM) with the LISREL 8.80 program. The research results show that partially, price perception has a negative but insignificant effect on consumer trust, while brand image has a positive and significant effect. Price perception and brand image also have a positive and significant influence on the decision to choose Ar-Rahman Excellent Junior High School. Brand image proved to be the most dominant variable in influencing the decision to choose. Additionally, consumer trust also has a positive and significant influence on this decision. Simultaneously, price perception and brand image explain 82.8% of the variation in consumer trust, while price perception, brand image, and consumer trust together explain 89.2% of the variation in the decision to choose.